The Influence of Profitability, Leverage and Company Size on Tax Avoidance in Energy Sector Companies - Milala, Nico; Darniaty, Will Andilla (Indonesia Banking School, 2024)
Tax avoidance is a practice aimed at managing tax expenditures to minimize the amount of tax that must be paid, while still complying with applicable legal regulations. This study uses Profitability (ROA), Leverage (DER), and Firm Size (SIZE) as independent variables that are suspected to influence Tax Avoidance (CETR) as the dependent variable. The research was conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. The data used is secondary data, derived from the financial statements of energy sector companies listed on the IDX. Sampling was done using a purposive sampling technique, with a sample size of 54 companies and a total of 270 observations. The obtained data were analyzed using multiple linear regression analysis techniques. The results of the study indicate that profitability has a significant positive effect on tax avoidance, leverage does not affect tax avoidance, while firm size has a significant positive effect on tax avoidance. The results of this study are expected to provide theoretical and practical contributions in the fields of taxation and financial management